Note—A Note on “Comparison of Computer Algorithms and Visual Based Methods for Plant Layout” by M. Scriabin and R. C. Vergin - Block, T. E. (Management Science, 1977)
This note recommends the use of flow dominance as a measure to determine the choice between computer algorithms and visual based methods for plant layout. It is suggested that plant layout problems with flow dominance close to or greater than 200% should be solved by visual based methods rather than computer algorithms. For the plant layout problems used by Scriabin and Vergin with a flow dominance greater than 200% visual based methods are superior to computer algorithms. It is shown by an experiment that for plant layout problems with a flow dominance less than 200% computer algorithms are superior to visual based methods.